Konstruksi Representasi Perempuan dalam Episode “Beauty Standard” Podcast in Her View: Analisis Wacana Kritis Perspektif Sara Mills - Ni Luh Made Gayatri Maharani Hartantya; Ni Putu Yunita Anggreswari; Ni Nyoman Sri Wisudawati; Ni Putu Intan Permatasari (LPPM Institut Pendidikan Nusantara Global, 2025)
Beauty standards in Indonesia have become a complex social construction shaped by globalization, media expansion, and cultural dynamics. This study analyzes how representations of women and beauty standards are constructed in the “Beauty Standard” episode of Pancatera’s In Her View podcast using Sara Mills’ Critical Discourse Analysis (CDA). The podcast, hosted by five Indonesian women from diverse backgrounds, creates a multi-voiced discursive space that reflects personal experiences and social critique. Focusing on the subject–object position and writer–reader positioning, this research employs a qualitative descriptive design by analyzing episode transcripts, observations, and interviews with selected listeners. The findings show that the hosts position themselves as active subjects who challenge dominant beauty norms and encourage self-acceptance and critical awareness. The audience is positioned as an equal participant, invited to reflect and engage emotionally with the narrative. The discourse produced in the episode constructs a counter-hegemonic narrative that resists narrow beauty ideals by highlighting diversity, self-reflection, and empowerment. This study contributes to feminist discourse, media representation research, and podcast studies by demonstrating how digital conversational media reshape beauty narratives in the Indonesian context.